Evidence of a role for Interleukin-6 in anoikis resistance and bioenergetic programming in oral squamous cell carcinoma - KARAVYRAKI, MARILENA (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2021)
Oral squamous cell carcinoma (OSCC) is the sixth most common type of cancer in the world and accounts for more than 90% of oral malignancies. Oral squamous cell carcinomas are usually preceded by oral premalignant lesions, mainly oral leukoplakia (OLK) after repeated insults of carcinogens, for instance tobacco and alcohol, which are considered to be the most important etiological factors in the development of oral cancer. OSCC arise from several anatomic sites within the oral cavity but most commonly from the oral, mobile tongue. Surgical removals of the tumour, radiation, and chemotherapy, are the usual treatment regimens against OSCC, however, they have not been satisfactory (Moore et al.,2000; Dong et al.,2015). Therefore, novel therapeutic targets for the treatment of oral cancer are required to be identified. Increased glycolytic flux is a common feature of cancer cells and thus enzymes of the glycolytic pathway are anti-cancer targets. Unrestrained cell proliferation, induced invasion and migration, deregulated cellular bioenergetics and apoptosis resistance are some of the hallmarks of cancer that resultin developing primary tumour growth, which consequently can lead to tumour propagation and to a secondary metastasis (Chaffer and Weinberg, 2011; Hanahan and Weinberg, 2011). Furthermore, cancer invasion, migration and anoikis(a form of apoptosis) resistance phenotypes are linked to increased glycolysis and decreased oxidative metabolism (Han et al.,2013). Cancer cells also interfere with the intracellular communication with the stromal environment and modulate various pathophysiological processes by secreting cytokines in the tumour microenvironment (TME), which have been observed to co-regulate tumour cell growth and metastasis (Joyce and Pollard, 2009; Kim et al.,2010; Pavlou and Diamandis, 2010; Balkwill et al.,2012; Swartz et al.,2012; Hartman et al.,2013; Kwon et al.,2015; Jayatilaka et al.,2017; Jayatilaka et al.,2018). In the current study, the bioenergetic profiles of normal primary gingival keratinocytes (PGK)with dysplastic oral keratinocytes (DOK) and squamous cell carcinoma (SCC-4) cells were compared. Results presented in this study demonstrated that despite the significant mitochondrial OCR, SCC-4 cells appeared to have dysfunctional mitochondria, when compared to DOK and PGK cells, as indexed by (a) increased extracellular acidification rate (b) reduced cellular NADH-dependent oxygen consumption and (c) suboptimal oxygen consumption per unit mass of mitochondria (d) reduced complex I activity and (e) higher glycolytic rate reflected in the greater iiiassociated with glycolysisintermediates. Furthermore, SCC-4 cells, compared to PGK and DOK cells, constitutively synthesized and released significant amounts of IL-6, which was further enhanced by the addition of the TLR2/TLR6 agonist, Pam2CSK4. The upregulated expression of TLR2/6 and IL-6Ra/gp130 receptors was also confirmed in SCC-4 cells. Examination of cancer phenotypes in pre-cancerous human tongue DOK cells and cancerous SCC-4 human tongue cells, includingmigration, invasion, anoikisresistance, markers of CSCs, markers of EMT, and cell death were also presented. Analysis of CSCs markers demonstrated that cancerous SCC-4 human tongue cellshave enriched CD44+/CD24−sub-populationand displayed a classic EMT profile unlike pre-cancerous human tongue DOK cells. Although migration was insensitive to IL-6 and independent to glycolysis, evidence showed invasion to be driven ultimately by glycolysis. A key finding was that IL-6 played a central role in promoting anoikisresistance, increasing glycolytic flux and inhibiting oxidative phosphorylation in SCC-4 cells. In conclusion, this study provided novel data and key insights into the bioenergetics of normal, dysplastic and cancerous oral cells, as well as uncovering a role for IL-6 in anoikis resistance, increased glycolytic flux and reduced oxidative phosphorylation in OSCC cells, warranting further studies on a therapeutic role for anti-IL-6 receptor antibodies for the treatment and metastasis of OSCC.
APPROVED
Keywords: oral cancer, human oral cancer, oral squamous cell carcinoma, OSCC, dysplasia, DOK, SCC-4, cancer metabolism, bioenergetics, cancer phenotype, cancer bioenergetics, anoikis resistance, interleukin-6, il-6